Decision support for trypanosomiasis - Robinson, Timothy P.; Hopkins, J. (European Union, 2001)
This paper anlayses the decision making process for trypanosomiasis control, describes some of the tools available to assist with decision making and concludes by discussing some opportunities for the future. Levels of decision making and examples of the stakeholders, the types of decisions made and the geographical scales to which these refer are illustrated, and factors to be considered at the different levels of decision making are outlined.